Acute and short-term insulin-induced molecular adaptations of GLUT2 gene expression in the renal cortex of diabetic rats - Freitas, Helayne Soares; D'Agord Schaan, Beatriz; Seraphim, Patricia Monteiro; Nunes, Maria Tereza; Machado, Ubiratan Fabres (Elsevier, 2005)
Increased GLUT2 gene expression in the renal proximal tubule of diabetic rats is an adaptive condition, which may be important in the diabetic nephropathy development. We investigated the effects of insulin treatment upon the renal GLUT2 overexpression of diabetic rats. Acute treatment, surprisingly, induced a rapid further increase in GLUT2 mRNA content. Twelve hours after insulin injection, GLUT2 mRNA was twice the value of saline-injected rats (P < 0.001), when GLUT2 protein remained unchanged. In response to short-term treatment, both GLUT2 mRNA and protein were increased in 1-day treated rats (P < 0.05 versus saline-injected), decreasing after that, and reaching, within 6 days, values close to those of non-diabetic rats. Concluding, insulin treatment induced: initially, an additional upregulation of GLUT2 gene expression, involving posttranscriptional modulation; thereafter, downregulation of GLUT2 expression, which returns to non-diabetic levels. The former may be related to increased insulin concentration, the latter may be due to glycemic control. © 2005 Elsevier B.V. All rights reserved.
Keywords: Alloxan; Diabetes; Glucose transporters; GLUT2 mRNA; GLUT2 protein (rat kidney); Insulin treatment; Nephropathy; glucose transporter 2; insulin; messenger RNA; sodium chloride; animal experiment; animal model; concentration response; controlled study; diabetes mellitus; drug effect; gene expression regulation; gene overexpression; genetic transcription; glucose blood level; glucosuria; insulin treatment; kidney cortex; male; nonhuman; Northern blotting; priority journal; rat; upregulation; Western blotting; Adaptation, Physiological; Animals; Blood Glucose; Diabetes Mellitus, Experimental; Gene Expression; Glucose Transporter Type 2; Hypoglycemic Agents; Insulin; Kidney Cortex; Male; Monosaccharide Transport Proteins; Rats; Rats, Wistar; Reverse Transcriptase Polymerase Chain Reaction; RNA, Messenger; Time Factors